Perfil molecular de diferentes cepas do subgênero Mundinia e cinética da visceralização por Leishmania enriettii em Cavia porcellus - Edneia Venancio Alves Sobrinho (2020)
Leishmania enriettii was first described in 1948 and, in 2016 it was reclassified into a new subgenus denominated Mundinia. In this subgenus, there are also other species such as Leishmania martiniquensis, Leishmania orientalis and Leishmania macropodum. In this study, we tried to establish phylogenetic relationships between three of these species and to provide a molecular technique for the rapid identification of these parasites. The cultured parasites were submitted to the PCR-RFLP technique with the primers for the hsp70 and ITS1 genes. The hsp70 gene fragment was sequenced and the dendogram produced. In this target, one of the strains of L. enriettii (Cobaia) was grouped in the Leishmania branch. This result caught our attention and we also decided to sequence the ITS1 gene fragment. In this target, the Cobaia strain of L. enriettii was grouped with those of the other species of the subgenus Mundinia. After successfully standardizing this PCR, it was further used to study visceralization in guinea pigs infected with L. enriettii L88 strain. Histological analyses of our group have already indicated this phenomenon in some organs (trachea, spleen, liver and lungs) at different times of infection (4, 8 and 12 weeks post infection). Thus, we extracted the DNA from paraffin blocks and performed the PCR targeting the hsp70 gene again. A clear kinetics was observed. Parasite's DNA was detected in the trachea and spleen after 4 and 8 weeks of infection. After 12 weeks, no DNA was detected. With these results in hands, an in vivo infection was performed in order to confirm the presence of the parasite in the spleen. After 6 weeks of infection, the animals were euthanized and organ fragments were collected (nasal mirror, lungs, spleen, liver and testicles). They were sown in NNN-LIT medium and observed until the parasites appearance. It was possible to isolate parasites only from spleen, confirming histology results. In conclusion, it was possible to distinguish the different strains / species of the subgenus Mundinia using the RFLP-PCR technique. This technique was effective in detecting parasite DNA in some organs. Our results showed that L. enriettii has tropism for the spleen. Our molecular data suggests that the Cobaia strain of L. enriettii has an unknown profile that should be better explored for a more correct taxonomic classification.